EXPLORING THE DEPTHS OF ENGLISH LITERATURE THROUGH JANE AUSTEN’S PRIDE AND PREJUDICE - Gaybullayeva M. (Bright Mind Publishing, 2025)
This scholarly article presents a comprehensive literary analysis of Pride and Prejudice, one of the most enduring and influential novels in English literature, written by Jane Austen. The paper investigates the novel within the broader context of English literary traditions and explores its contribution to the development of the 19th-century realist novel. The article provides an in-depth exploration of the novel’s two protagonists, Elizabeth Bennet and Mr. Darcy, as well as supporting characters such as Mr. And Mrs. Bennet, Jane Bennet, Mr. Bingley, Mr. Wickham, and Lydia Bennet. Their character development is examined through a psychological and socio-cultural lens, highlighting the author’s use of irony, free indirect discourse, and nuanced dialogue. The structure and style of Austen’s writing are analyzed to illustrate how her narrative techniques support thematic exploration and reader engagement.
Keywords: English literature, Jane Austen, Pride and Prejudice, character analysis, 19th-century novel, social class, irony, Elizabeth Bennet, Mr. Darcy, romantic fiction.